RANCANG BANGUN IOT MENGGUNAKAN SIM900A PADA SISTEM INFORMASI TAGIHAN AIR ARTETIS METODE WATER FLOW (Lembaga Pengembangan Kinerja Dosen, 2021)
Internet of Things (IoT) is a dynamic global network infrastructure with standard configuration capabilities and interoperable communication protocols where physical and virtual